Pengembangan Permainan Edukatif Tebak Bendera Berbasis windows Phone - An'im Almiktad; R. Rizal Isnanto; Ike Pertiwi Windasari (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2016)
There is still a lack of the use of technology in the learning process, so that the teachers are active only explain but the child passively because just listen and pay attention to the material presented. Conventional teaching methods result in children less excited and more easily bored in learning. Theacer supposed to be able to utilize the technology to be applied in the learning process so as to enhance the child's enthusiasm for learning and teaching children to play an active role in learning. Based on these problems built an application Multimedia Interactive Learning based windows phone to be able to support the learning processin children. The Learning Multimedia Applications built using software construct 2, and Adobe Photoshop cs5. The method used is a multimedia development Multimedia Development Life Cycle (MDLC). For application testing method using the Black Box Testand Likert Scale questionnaireform.